2021
DOI: 10.1038/s42005-021-00551-1
|View full text |Cite
|
Sign up to set email alerts
|

Massively-multiplexed generation of Bell-type entanglement using a quantum memory

Abstract: High-rate generation of hybrid photon-matter entanglement remains a fundamental building block of quantum network architectures enabling protocols such as quantum secure communication or quantum distributed computing. While a tremendous effort has been made to overcome technological constraints limiting the efficiency and coherence times of current systems, an important complementary approach is to employ parallel and multiplexed architectures. Here we follow this approach experimentally demonstrating the gene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…Unfortunately, the reported scheme 38 to encode the memory qubit is complex and very difficult to use for multiplexing. Very recently, a spatially multiplexed DLCZ-type quantum memory generating Bell-type entanglement was demonstrated in cold atoms 74 . Using a spatially resolved single-photon camera, the work achieved large-scale multimode quantum correlations between Stokes and anti-Stokes photons, with lifetimes up to 50 µs.…”
mentioning
confidence: 99%
“…Unfortunately, the reported scheme 38 to encode the memory qubit is complex and very difficult to use for multiplexing. Very recently, a spatially multiplexed DLCZ-type quantum memory generating Bell-type entanglement was demonstrated in cold atoms 74 . Using a spatially resolved single-photon camera, the work achieved large-scale multimode quantum correlations between Stokes and anti-Stokes photons, with lifetimes up to 50 µs.…”
mentioning
confidence: 99%
“…87 Rb, with a memory lifetime of about 28 µs [7]. Using a single-photon resolving camera Parniak et al [8] showed non-classical storage in up to 665 spatial modes for up to 50 µs in 87 Rb, and more recently bipartite entanglement across 500 modes [41]. However, none of these experiments involved a telecom-compatible photon, which would also require interfacing the memory with a quantum frequency converter [42].…”
Section: Resultsmentioning
confidence: 99%
“…Given the configuration of laser beams, i.e., angle between coupling and signal light, the atomic coherence has a 50 rad/mm transverse wavevector component. This gives ≈260 μs of thermal-motion-limited storage time 60 . The control field-induced spin-wave decay rate 37 in the experiment is about 10kHz.…”
Section: Methodsmentioning
confidence: 99%